Mathematical Analysis of the Suppression of Atmospheric Impulses in Distribution Systems - Quimiz, Josue (2021)
The study and analysis of the suppression of atmospheric impulses to the lightning rod of an Electrical Distribution System was carried out, based on the comparison of theoretical results developed with the Matlab – Simulink software and the experimental ones carried out in the High Voltage laboratory of the Salesian Polytechnic University of Ecuador, in order to understand the electrical and mathematical behavior of the protection to the distribution system. The equivalent circuit of the IEEE frequency-dependent model "Modeling of metal oxide surge arresters”was used. The mathematical analysis consisted in constructing the equations of the equivalent circuit and using the Matlab tool that extrapolates with the best approximation the behavior of the nonlinear resistances of the beam, in addition, the atmospheric impulse generating circuit defined in the ANSI/IEEE Standard 4-1995 standards required for suppression was modeled.